brownfield - Grigoryeva, Elena (project baikal, 2018)
The theme of the session of Baikal Winter University of Town Planning Design was conversion of Zaton, a district in the center of Irkutsk, which has changed its meanings several times during its long history. Fatefully cut off from the mainland by Transsib at the turn of the 20th century, the peninsular is located where the Irkut meets the Angara. Zaton has ceased to develop and now does not look like a central part of the city, regardless its geographical location. Developers prefer greenfields, vacant areas, but not Zaton with its warehouses, sawmills and dockyards. At the same time it has neither networks nor roads. It is obvious that as soon as infrastructure appears the land will become precious because of its central location and the water.International teams of the Winter University proposed their ideas, which were preceded by students’ works of previous years presented by the teachers of the Institute of Architecture and Construction of Irkutsk National Research Technical University.
Keywords: Baikal Winter University of Town Planning Design; Baikal; Irkutsk; Irkutsk National Research Technical University; Zaton